Brain-wide input-output analysis of tuberal nucleus somatostatin neurons reveals hierarchical circuits for orchestrating feeding behavior - Esra Senol; Menghan Wang; Yongjuan Xin; Zhuolei Jiao; Hasan Mohammad; Xin Yi Yeo; Tengxiao Si; David M. Young; Hua Huang; Yingxue Wang; Qin Li; Sang Yong Jung; et al. (Nature Communications)
Abstract Feeding is an innate behavior critical for survival but is also influenced by many non-nutritional factors such as emotion, social context and environmental conditions. Recently, tuberal nucleus somatostatin (TNSST) neurons have been identified as a key feeding regulation node. To gain a deeper understanding of the TNSST neural networks, we quantitatively characterised the brain-wide input-output configuration of mice TNSST neurons using the VITALISTIC method (Viral Tracing Assisted by Light-Sheet microscope and Tissue Clearing) and single-cell projectomes by fluorescence micro-optical sectioning tomography (fMOST). We found that TNSST neurons receive direct inputs from and send outputs to a broad range of brain regions, including many cortical and subcortical areas. Differently from AgRP neurons, the extensively studied ‘hunger’ neurons, TNSST neurons receive more diverse inputs from extra-hypothalamic regions and neuromodulatory centers. Using the projection-specific input tracing, we further revealed fine-tuning of the input-output configuration of TNSST neurons that align with specific functional needs.